(3TQM ThGgO TQM GdJMaI GdhQOjIs - (3GdHZOGOj, YHO GdbGOQ Hf YeQ, J(B1093(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi CaVd GdeQSdjfhHYO ajbhdYHO GdbGOQ Hf YeQ GdHZOGOj gPG TQM ThGgO TQM GdJMaI GdhQOjI ddYGdeRjf GdOjf YeQ GdTgjQ HGHf GdhQOjs
(3BNQgG (B:s
(3hhVYJ GdLf GdUMjaI GdJj ajgG GdbUjOI JMJ QCSg hGddg CYdes
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B1087(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 2 / 192s
(3gOjI GdYGQajf(B: 1 / 602s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs